Intercultural Competence in Students’ Scientific Work at Nahdlatul Ulama Islamic University Jepara - Mahalli; Khalimatus Sa’diyah; Aliva Rosdiana; Sukarman (Jurnal Pendidikan Indonesia, 2025)
One of the provisions in writing scientific papers is that there must be references in foreign languages. The problem arises that students have difficulty in capturing accurately and properly the message or meaning written in foreign language references due to differences in cultural context between Indonesian and foreign languages. This study aims to investigate the role of intercultural competence in writing scientific papers by students at the Nahdlatul Ulama Islamic University of Jepara. This study uses a qualitative research design with observation techniques, semi-structured interviews, and literature studies. Data analysis uses content analysis techniques. The participants observed were all 22 seventh semester students and 3 supervisors of writing scientific papers/thesis. The results of the study indicate that intercultural competence is very necessary to be taught to students who are completing scientific papers so that students can properly understand foreign language literature. The second finding revealed that there was a real impact of the role of intercultural competence in compiling scientific papers, namely increasing students' understanding of foreign language reference sources. The implication of the research results is that universities need to include intercultural competence in the study program curriculum.